Spatial divergence between self-rated health and body mass index in China: Exploring the role of economic status using China Family Panel Studies (CFPS) 2016 and 2020 - Jiayin Liu; Peizhi Yu; Xiaoyu Ye; Yirui Yang; Zhixin Feng (PLoS ONE, 2025)
Health disparities across China remained a major public health concern, with both individual and regional economic conditions shaping variations in health outcomes. In the context of the “Healthy China 2030” initiative, this study used data from the 2016 and 2020 waves of the China Family Panel Studies (CFPS) and applied multivariate multilevel logistic regression models to examine the associations between economic status at the individual and province levels and two key health indicators: self-rated health (SRH) and body mass index (BMI). The results showed that, at the individual level, a higher total value of durable consumer goods was negatively associated with having a normal BMI, whereas higher travel expenditure, per capita living space, and total cash and deposits were associated with a greater likelihood of reporting good SRH. At the province level, higher mean income exhibited a negative association with normal BMI and moderated the effects of household economic resources: income growth reduced health disparities in some dimensions (e.g., living space, cultural and entertainment spending) but widened them in others (e.g., vehicle purchase expenses). Spatial mapping further indicated that southern provinces tended to exhibit healthier BMI distributions but lower levels of good SRH compared with northern regions, revealing a clear spatial divergence between subjective and objective health measures. These findings highlighted the complex, multilevel, and spatially uneven relationships between economic status and health in China. Policy efforts should aim to strengthen household economic resilience, reduce regional health inequalities, and tailor interventions to local contexts to promote health equity nationwide.